ChemInform Abstract: Morphotropy and Temperature‐Driven Polymorphism in A2Th(AsO4)2 (A: Li, Na, K, Rb, Cs) Series. Issue 52 (29th December 2014) - Yu, Na; Klepov, Vladislav V.; Modolo, Giuseppe; Bosbach, Dirk; Suleimanov, Evgeny V.; Gesing, Thorsten M.; Robben, Lars; Alekseev, Evgeny V.
Abstract M2Th(AsO4)2 (M: Li, Na, K, Rb, Cs) single crystals are prepared by solid state reaction of Th(NO3)4, NH4H2AsO4, and MNO3 (Pt crucible, 1123—1273 K, controlled cooling).